Discovery and biodegradation characterization of polyethylene by Metabacillus niabensis - Sardar, Raj Kumar (Frontiers in Microbiology, 2025)
Polyethylene (PE), a type of plastic, is the primary contributor to persistent and prolonged environmental contamination. Plastic biodegradation is considered a promising approach to addressing current environmental issues. In this study, 300 marine isolates were evaluated for their ability to biodegrade PE. Based on total cellular fatty acid profiling and 16S rRNA gene sequence homology, RS120 was identified as Metabacillus niabensis (M. niabensis) among positively tested marine strains. Furthermore, early bacterial attachment to the PE surface was observed during the biotreatment. Then, after, chemical structural changes before and after the biodegradation were shown by the disappearance of the larger hydrocarbon tetra-tetracontane (C44H20) and the emergence of the smaller hydrocarbon heptadecane (C17H36), tetracosane, benzene, 1,1′-(cyclobutanediayl) (C16H16), and 2-tert-butyl-4-6-bis (3-5-di-tert-butyl). After that, Fourier Transform Infrared Spectroscopy (FTIR) spectra designated two new, shouldered peaks at 2590 cm−1 and 2,610 cm−1 along with a longer, sharper, and pointed peak at 2361 cm−1 in weathered PE, which substantiates significant alteration in chemical structure. Moreover, significant variation in thermal stability and crystallinity of plastic was also investigated. According to the enzymatic studies, bacterial peroxidase and dehydrogenase activities during treatment were higher at 30 days of treatment. In the meantime, the weight loss of the film was regularly monitored, and within 30 days of co-incubation with RS120, about 3.3% of its initial weight had been lost. These findings showed that the strain partially degrades the PE film when used as the sole carbon source. The results revealed that M. niabensis is reported here for the first time as an efficient PE degrader.